2015
DOI: 10.1016/j.cej.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Microreactors technology for hydrogen purification: Effect of the catalytic layer thickness on CuO /CeO2-coated microchannel reactors for the PROX reaction

Abstract: Two blocks of microreactors composed by 100 microchannels and coated, respectively, with 150 and 300 mg of a CuO x /CeO 2 catalyst, were prepared and tested in the preferential oxidation of CO in presence of H 2 (PROX). The deposition of different amount of catalyst resulted in different catalytic layer thicknesses thus modifying the catalytic performances of the microreactor. The evaluation of the main reaction variables (the space velocity, the O 2 -to-CO ratio and the presence of H 2 O and/or CO 2 in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…For instance, Laguna et al [17] recently demonstrated the absence of significant diffusional limitations controlling the catalytic performances for layer thicknesses around 10 m. Moreover, Potemkin et al [36] established a limit slightly higher for the layer thickness, above 20 m, for which the diffusional processes does not control the reaction rate .…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Laguna et al [17] recently demonstrated the absence of significant diffusional limitations controlling the catalytic performances for layer thicknesses around 10 m. Moreover, Potemkin et al [36] established a limit slightly higher for the layer thickness, above 20 m, for which the diffusional processes does not control the reaction rate .…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…Considering that those processes are controlled by the layer thickness, the use of micromonolithic structures should improve the diffusional processes and allow a better control of the reaction through an appropriate catalytic layer thickness providing a better temperature control hindering the hot spot formation [16,17]. Therefore, the layer thickness should be well-controlled in order to maintain the enhancement of the transport phenomena provided by the micromonoliths.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, coating monoliths by solution-combustion synthesis has given materials with good catalytic performance for the PrOx reaction in the presence of H 2 O and CO 2 [295,296]. Other properties that should be optimized to enhance the performance of copper/ceria monolithic catalysts include the coating thickness [297] and cell density of the structure [293].…”
Section: Preferential Oxidation Of Carbon Monoxidementioning
confidence: 99%
“…The catalyst coating methods for the wash‐coated microchannel reformers are out of the scope of this review paper; however, interested readers can refer to other studies …”
Section: Methanol Reformingmentioning
confidence: 99%